SOSIALISASI HILANGKAN PRANK OJEK ONLINE MENJADIKAN INDONESIA NEGARA KEMANUSIAAN - Renny Christiarini; Amanda Rosetia; Nur Hidayati; Billy Shevriyanto; Eva Noorliana; Febry Supriyanto; Nico Dwi Putra; Ellin Ellin; Agika Wasinta Br Sembiring; Octa Villa; Febri Tegar Siswoyo (National Conference for Community Service Project (NaCosPro), 2020)
COVID-19 has a real impact on the Indonesian economy, this makes it difficult to meet daily needs, especially for the lower middle class. In the midst of the difficulty of finding income to meet daily needs, the sense of humanity in Indonesia actually looks fading. The online motorcycle taxi prank is real proof that human values ​​in Indonesia have started to cause concern. Difficult to meet the needs of life that depends on orders from the paracustomer at this time COVID19, it was made worse by the actions of prank deliberately carried out by the customers. This research was conducted to overcome this. Campaigns related to the socialization of invitations to eliminate the presence of prank on online motorcycle taxi through videos and also posters that are inviting are prototypes used to solve problems. This socialization is intended to help rebuild human values ​​in Indonesia from a scope that is not realized by many people. Through this activity, it is hoped that it can help the creation of humanity's value again in Indonesia, specifically helping to create mutual understanding between online motorcycle taxis and customers.